Efficacy and safety of semaglutide on weight loss in obese or overweight patients without diabetes: A systematic review and meta-analysis of randomized controlled trials - Gao, Xueqin; Hua, Xiaoli; Wang, Xu; Xu, Wanbin; Zhang, Yu; Shi, Chen; Gu, Ming (Frontiers in Pharmacology, 2022)
Objectives: To explore the weight loss effect and safety of semaglutide as a conventional anti-obesity drug systematically in obese or overweight patients without diabetes. Methods: The randomized controlled trials (RCTs) of semaglutide in obese or overweight patients without diabetes were retrieved from PubMed, Cochrane Library, EMBASE and ClinicalTrials.gov from database inception until May 2, 2022. Data extraction and quality assessment of studies meeting the inclusion criteria were performed and statistical analysis was conducted by Review Manager 5.3 and Stata 14. Results: Eight studies involving 4567 patients were enrolled in the meta-analysis. Compared with placebo, semaglutide induced a significantly body weight loss (MD: -10.09%; 95% CI: -11.84 to -8.33; P＜0.00001), elicited a larger reduction in body mass index (MD: -3.71 kg/m2; 95% CI: -4.33 to -3.09; P＜0.00001) and waist circumference (MD: -8.28 cm; 95% CI: -9.51 to -7.04; P＜0.00001), achieved weight loss of more than 5%, 10%, 15% and 20% with a higher proportion of participants. Semaglutide exhibited a positive effect on blood pressure, C-reactive protein and lipid profiles, expressed more adverse effects than placebo, mainly gastrointestinal reactions. The results were stable and reliable with dose-dependence. Conclusions: Semaglutide indicated a significant weight loss with an acceptable safety for obese or overweight patients without diabetes.